Model of protective behavior during the COVID-19 pandemic in Indonesia - Agung, Ivan Muhammad; Husni, Desma (International Journal of Public Health Science (IJPHS), 2023)
To prevent coronavirus disease 2019 (COVID-19) from spreading extensively and rapidly during the pandemic, protective behaviors are crucial. This study aimed to determine the influence of risk perceptions, health care, social influences, and intentions on the improvement of protective behaviors during the COVID-19 pandemic. There were 325 participants consisting of 74 men and 251 women (mean age (M)=21.47, SD=6.8). Based on previous studies, measurements were conducted using a variety of questionnaires. The hypotheses were examined by data analysis using structural equation modeling (SEM). The results show that the proposed model met the established criteria. It is interesting to note that risk perceptions influence how protective behaviors are improved through health care and intentions. The social influences on protective behaviors, meanwhile, are both directly and partially mediated by intentions. In conclusion, health care and intentions serve as mediators between risk perceptions and protective behaviors rather than being directly associated. Health care, however, is unrelated to intentions. Furthermore, social influences are the most dominant factor in improving protective behaviors during COVID-19 pandemic. Therefore, it may serve as a preliminary justification for the government to promote for a policy that addresses social influences in order to improve protective behaviors.